2005
DOI: 10.1002/chir.20112
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of chiral sulfinates using chiral diamines

Abstract: The reaction of p-toluenesulfinyl chloride with alcohols in the presence of chiral diamines was examined. Chiral sulfinates were obtained in good yields with enantioselectivity up to 76% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…We conclude that their reaction with sulfonyl chloride is slow but quite rapid with the corresponding sulfinyl chloride or other active sulfinylating agent formed in the reaction mixture. A chiral amine (entry 13) and chiral sulfoximine (entry 17) afforded reasonable yields of sulfinyl derivatives, but no diastereoselection was found . It is not immediately clear why pyrollidine (entry 8) and propargylamine (entry 16) reacted so poorly, but for the former, a considerable amount of sulfonamide was isolated.…”
mentioning
confidence: 99%
“…We conclude that their reaction with sulfonyl chloride is slow but quite rapid with the corresponding sulfinyl chloride or other active sulfinylating agent formed in the reaction mixture. A chiral amine (entry 13) and chiral sulfoximine (entry 17) afforded reasonable yields of sulfinyl derivatives, but no diastereoselection was found . It is not immediately clear why pyrollidine (entry 8) and propargylamine (entry 16) reacted so poorly, but for the former, a considerable amount of sulfonamide was isolated.…”
mentioning
confidence: 99%
“…Chiral sulfinate are used as precursors of chiral sulfoxide by addition of an organometallic reagent (Andersen's method) . In 2005, Toru et al reported the addition of tert- butyl alcohol onto p -toluenesulfinyl chloride 488 in the presence of a stoichiometric amount of chiral diamines (Scheme ) . The best result was obtained with 2 equiv of diamine 492 , which produced the corresponding sulfinate 489 in 76% ee.…”
Section: 16 Addition To Sulfinyl Chloridementioning
confidence: 99%
“…For example, sulfinic esters were recently applied as efficient sulfenylating agents 7 and sulfonic esters as sulfonylating agents. 8 The classical methods for the synthesize of these classes of organosulfur compounds involve the reaction of sulf(o,i)nyl chlorides, 9,10 sulf(o,i)nic acids, 11,12 or sodium sulfonates 13 with alcohols. However, corrosion, instability, and/or difficult preparability of some of the sulf(i,o)nylating agents limited the utility of these methods.…”
Section: Introductionmentioning
confidence: 99%